2017
DOI: 10.1089/cyber.2017.0107
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality Game to Assess Obsessive-Compulsive Disorder

Abstract: The retrospective and subjective nature of clinical interviews is an important shortcoming of current psychiatric diagnosis. Consequently, there is a clear need for objective and standardized tools. Virtual reality (VR) can be used to achieve controlled symptom provocation, which allows direct assessment for the clinician. We developed a video VR game to provoke and assess obsessive-compulsive disorder (OCD) symptoms in a standardized and controlled environment. The first objective was to evaluate if the VR ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…Van Bennekom et al created a VR game from a first-person perspective that allowed patients to walk through a house where 15 OCD-related items were displayed, while simultaneously measuring their OCD symptoms (compulsions, anxiety, tension, uncertainty, and urge to control). A pilot study comparing 8 patients with OCD and 8 healthy controls showed that VR is capable of triggering OCD symptoms in patients, allowing clinicians to directly observe and assess OCD symptoms [27].…”
Section: Resultsmentioning
confidence: 99%
“…Van Bennekom et al created a VR game from a first-person perspective that allowed patients to walk through a house where 15 OCD-related items were displayed, while simultaneously measuring their OCD symptoms (compulsions, anxiety, tension, uncertainty, and urge to control). A pilot study comparing 8 patients with OCD and 8 healthy controls showed that VR is capable of triggering OCD symptoms in patients, allowing clinicians to directly observe and assess OCD symptoms [27].…”
Section: Resultsmentioning
confidence: 99%
“…Derleme çalışmalar, kontrol grupsuz deneysel çalışmalar, randomize kontrollü çalışmalar hatta son dönemde meta analiz çalışmaları bu alandaki çalışmalara örnektir. SG uygulamaları post travmatik stres bozukluğu, [6][7][8][9][10] obsesif kompulsif bozukluk, [11][12][13] alkol kötüye kullanımı, [14] yeme bozuklukları ve beden imajı ile ilgili problemler [15,16] ve şizofreni [17,18] gibi birçok alanda kullanılmaktadır. SG uygulamaları bu çalışmalarda zaman zaman bir müdahale yöntemi, zaman zaman bir tanı koyabilme aracı olarak kullanılmıştır.…”
Section: Sanal Gerçeklik (Sg) Uygulamalarının Psikolojik Yardım Alanıunclassified
“…A pilot study comparing eight patients with OCD and eight healthy controls showed that VR is capable of triggering OCD symptoms in patients, allowing clinicians to directly observe and assess OCD symptoms [24].…”
Section: Vr-based Assessmentmentioning
confidence: 99%